Medicine and Sport Science 2008
DOI: 10.1159/000134298
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi Chuan in the Management of Parkinson’s Disease and Alzheimer’s Disease

Abstract: Strategies of exercise adaptation include use of Tai Chi-like exercise for individuals with ALZ and those in middle or late stages of PD as well as providing instructional resources and training for caregivers and exercise aides to facilitate practice as a part of daily life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Used as a clinical treatment, TCC has demonstrated potential benefits for people with chronic neurological diseases such as PD (Allen et al, 2011), AD (Klein, 2008), multiple sclerosis (MS), and mood disorders (Payne and Crane-Godreau, 2013; Wang et al, 2014). On a behavioral level, several cross-sectional and longitudinal studies have confirmed the positive effect of mind-body practice, mainly on cognitive control.…”
Section: Introductionmentioning
confidence: 99%
“…Used as a clinical treatment, TCC has demonstrated potential benefits for people with chronic neurological diseases such as PD (Allen et al, 2011), AD (Klein, 2008), multiple sclerosis (MS), and mood disorders (Payne and Crane-Godreau, 2013; Wang et al, 2014). On a behavioral level, several cross-sectional and longitudinal studies have confirmed the positive effect of mind-body practice, mainly on cognitive control.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies suggest the potential benefits of tai chi to age-related decline as a result of pulmonary disease, 13 Parkinson’s disease, 14 problems concerned with balance, 15 and psychological well-being. 16 These studies suggest that tai chi is safe for older adults and an enjoyable activity, with potential for long-term adherence and exercise compliance.…”
Section: Introductionmentioning
confidence: 99%
“… 17 The literature suggests using easy-to-follow, tai chi-like exercise rather than traditional tai chi practice for people with dementia. 14 This pilot study therefore used simplified TCQ as an exercise aiming to investigate its preliminary effects on night-time sleep in older adults with cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Verschiedene weitere interessante Ansätze, wie Boxen [23], Tai Chi [25,67,77,79,98], Vibrationstraining [22,27,34,73,115], stochastische Resonanztherapie [51,65,122], Yoga oder Tanzen [32,33,54,55,56,82], werden mittlerweile in der Therapie durchgeführt. Alle können bei richtiger Dosierung vielleicht eine Fitnesssteigerung hervorrufen.…”
Section: Schnelligkeitstrainingunclassified